2015
DOI: 10.1155/2015/818043
|View full text |Cite
|
Sign up to set email alerts
|

Standard Triple Therapy versus Sequential Therapy inHelicobacter pyloriEradication: A Double-Blind, Randomized, and Controlled Trial

Abstract: Aim. To compare 10-day standard triple therapy versus sequential therapy as first-line treatment in patients infected with H. pylori. Methods. One hundred H. pylori positive patients (diagnosed by rapid urease test and histology), with average age of 47.2, M/F = 28/72, were randomized to receive either standard triple treatment (TT) as follows: lansoprazole 30 mg, clarithromycin 500 mg, and amoxicillin 1 g, b.i.d. for ten days, or sequential treatment (ST) as follows: lansoprazole 30 mg, amoxicillin and placeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…This therapy is complex, highly variable in different regions, and the results are similar to those of concomitant therapy and 14day triple therapy (390) . In Brazil, a study comparing sequential therapy showed that the rate of eradication of HP (86%) was similar to that of standard triple therapy for 10 days (391) . Furthermore, data on the outcomes of hybrid therapy (PPI associated with amoxicillin for 5-7 days followed by PPI, amoxicillin, clarithromycin, and metronidazole for another 5-7 days) as the first-line option are limited and inconsistent (40) .…”
Section: Level Of Evidence: 2amentioning
confidence: 88%
“…This therapy is complex, highly variable in different regions, and the results are similar to those of concomitant therapy and 14day triple therapy (390) . In Brazil, a study comparing sequential therapy showed that the rate of eradication of HP (86%) was similar to that of standard triple therapy for 10 days (391) . Furthermore, data on the outcomes of hybrid therapy (PPI associated with amoxicillin for 5-7 days followed by PPI, amoxicillin, clarithromycin, and metronidazole for another 5-7 days) as the first-line option are limited and inconsistent (40) .…”
Section: Level Of Evidence: 2amentioning
confidence: 88%
“…In addition, several studies conducted in different countries have compared 10 days of ST with 7 days of TT and have demonstrated some favorable results for ST; a trial from Ireland found a superior result for ST (68% vs. 55%) (22). A study from Taiwan also showed a favorable result for ST, whereas a study from Brazil found equal eradication rates (86%) for both regimens (21,23).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence also showed no significant difference in eradication rates in standard triple drug therapy (87.8%) and sequential drug therapy (89.6%) concluding that both the regimens were equally effective. 42 Several studies in the literature have shown that the effectiveness of the standard triple drug therapy has been declining over the past years, mainly due to clarithromycin resistance, especially in the USA and Europe. [43][44][45] For this reason, sequential therapy has been assessed, with eradication rates greater than 90% as study conducted previously.…”
Section: Discussionmentioning
confidence: 99%